Subject Learning in the Primary Curriculum - Bourne, Jill; Briggs, Mary; Murphy, Patricia; Selinger, Michelle; Bourne, Jill; Briggs, Mary; Murphy, Patricia; Selinger, Michelle (Taylor & Francis, 1995)
The emphasis on subject knowledge in primary curricula is a world-wide phenomenon and has become increasingly the focus of attention in England, with the introduction of the National Curriculum and the appointment of subject co-ordinators in schools. Yet what exactly constitutes a subject and its practice remains controversial. The book is organised into five parts. Part one examines the general aims of primary education, in order to give a background for a more detailed exploration of UK curriculum development. Parts two, three and four examine the core subjects of Eng, science and mathematics, whilst constantly bearing in mind the full range of views about the purpose of education and the nature of knowledge. Part five introduces key debates about approaches to knowledge, and raises issues about the future organisation of the curriculum. Subject Learning in the Primary Curriculum is the OU reader for Module 832, Teaching and Learning in the Primary Core Curriculum in the MA in Education.
English
Keywords: Education; education; cognitive; apprenticeship; national; science; procedural; understanding; cross-age; studies; good